Development of an RME-Based Hypothetical Learning Trajectory of Least Common Multiple for Elementary School Students - Rika Cintya Napitupulu; Jesi Alexander Alim; Neni Hermita; Berdriati Ibrahim (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2021)
This study aims to develop an RME-based hypothetical learning trajectory of least common multiple for elementary school students. This study used research & development based on the Plomp development model. The subjects of this study were 9fourth grade elementary school students in Pekanbaru, Riau. The data of this study was collected by distributing questionaires and conducting interviews. The data collected was analysed by using descriptive and quantitative analysis. The results indicated that the hypothetical learning trajectory developed was very valid with an average score of 84.37% and was very practical with an average score of 89.38% from the students and 88.89% from the teachers. Therefore, the RME-based hypothetical learning trajectory of least common multiple can be further used by elementary school students and teachers.